Reliable finite-time sliding-mode control for singular time-delay system with sensor faults and randomly occurring nonlinearities - Liu, Yangfan; Ma, Yuechao; Wang, Yanning (Applied mathematics and computation, 2018)
This paper focuses on the finite-time sliding-mode control problem for singular time-delay system with sensor failures and uncertain nonlinearities. Based on the proposed sliding-mode control law, sufficient criteria are provided to guarantee the closed-loop system is singular sliding-mode finite-time boundedness in both reaching phase and sliding motion phase. The prescribed sliding-mode control law can drive the state trajectories onto the specified sliding surface in a short time interval. Furthermore, the singular H∞ finite-time boundedness conditions for error system have been established with sensor faults over the whole interval. Through the linear matrix inequalities technique, gain matrices for controller and estimator can be obtained. Finally, numerical examples have been given to demonstrate the potentials of the proposed method.